The Reification of Non-Human Animals - Caprioglio Panizza, Silvia (My University, 2022)
This paper takes up Axel Honneth’s suggestion that we, in the 21st century Western world, should revisit the Marxian idea of reification; unlike Honneth, however, this paper applies reification to the ways in which humans relate to non-human animals, particularly in the context of scientific experiments. Thinking about these practices through the lens of reification, the paper argues, yields a more helpful understanding of what is regarded as problematic in those practices than the standard animal rights approaches. The second part of the paper offers ways of overcoming reification that go beyond Honneth’s idea of recognition by introducing Iris Murdoch’s idea of attention. This proposed strategy makes the ethical relevance of reification more salient and makes it possible to counter reification through a practice such as attention which, unlike recognition, can be consciously established.
Reifikace zvířat jiných než člověk
Keywords: reification; Axel Honneth; non-human animals; animal experimentation; reifikace; Axel Honneth; nehumánní zvířata; pokusy na zvířatech